2008
DOI: 10.1021/ol8001283
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangement of a Cyclohexyl Radical to a Cyclopentylmethyl Radical on the Avermectin Skeleton

Abstract: The rearrangement of a substituted cyclohexyl radical to a cyclopentylmethyl radical on the skeleton of avermectin B1 was observed experimentally and explored computationally. The Stork-Nishiyama methodology was applied to the macrocycle of interest followed by a Tamao oxidation. The expected 5-6 fused ring product was observed in minor amounts. The major product was a 5-5 fused ring resulting from apparent conversion of the initially formed cyclohexyl radical to a cyclopentylmethyl radical. Preliminary comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 45 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Rather than a 1,2-shift, this rearrangement occurred via a series of cascading radical processes (Scheme 31). 64 Wille and coworkers report formation of bicyclic ketones (after hydrolysis) via a radical translocation/cyclization cascade initiated by nitrogen-centered radicals (aminium or amidyl, Scheme 32). 65 Other noteworthy examples of multistep radical rearrangements were reported, and the interested reader is directed to the pertinent reports for the details.…”
Section: Scheme 30mentioning
confidence: 99%
“…Rather than a 1,2-shift, this rearrangement occurred via a series of cascading radical processes (Scheme 31). 64 Wille and coworkers report formation of bicyclic ketones (after hydrolysis) via a radical translocation/cyclization cascade initiated by nitrogen-centered radicals (aminium or amidyl, Scheme 32). 65 Other noteworthy examples of multistep radical rearrangements were reported, and the interested reader is directed to the pertinent reports for the details.…”
Section: Scheme 30mentioning
confidence: 99%
“…We recently reported on our studies dedicated towards understanding structure-activity relationships of Avermectin B 1 , 1 , the extraordinary, highly potent macrolide discovered more than two decades ago at Merck 4,5. During the synthesis of an Avermectin analogue, an apparent radical ring-cleavage followed by a ring-closure produced a ring-contracted product, Scheme 1 5.…”
Section: Introductionmentioning
confidence: 99%
“…During the synthesis of an Avermectin analogue, an apparent radical ring-cleavage followed by a ring-closure produced a ring-contracted product, Scheme 1 5. This rearrangement from a cyclohexyl radical to a cyclopentylmethyl radical was unforeseen, since previous reports demonstrated that tin hydride typically traps the cyclohexyl radical 1o,6…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silylation of cyclopentenol 14 with (bromomethyl) chlorodimethyl silane 15 yielded the bromosilyl ether, which was directly subjected to the radical cyclization . Intramolecular radical cyclization of the labile silyl ether intermediate with Et 3 B and Bu 3 SnH afforded the desired cis -fused oxasilole 16 in good yield.…”
mentioning
confidence: 99%